Pengaruh Ekowisata Terhadap Perekonomian Masyarakat Desa Bijeli, Kecamatan Noemuti, Kabupaten Timor Tengah Utara, Provinsi Nusa Tenggara Timur - Neti Nenabu; Paulus Un; Nixon Rammang (Wana Lestari, 2023)
Ecotourism is a tourism sector that has the potential to support the economy, from ecotourism local governments can also use it to increase local income. The purpose of this study was to determine the supporting facilities, available potential, and income levels in Oeluan ecotourism, Bijeli Village, North Central Timor District.This research was conducted in the Oeluan Ecotourism Area, North Central Timor Regency using primary and secondary data and survey methods namely interviews, observation, questionnaires, and documentation by determining respondents using the Non Probability Sampling technique. The collected data were analyzed qualitatively, descriptively, potential analysis, and quantitative analysis.The results of the study obtained that facilities at Oeluan ecotourism can support tourist attraction. The potential available in Oeluan ecotourism is potential based on government policies, physical conditions, namely flora and fauna and natural panorama, based on location/accessibility and based on visitors. Regional Original Revenue (PAD) obtained by the management in 2019 and 2020 amounted to Rp.45.500.000, while in 2021 it was Rp.41.500.000 and income by traders was Rp.86.352.000 with an average of Rp.5.756.000. After being analyzed using the R/C ratio, Oeluan ecotourism provides benefits for the surrounding community.